Correlation Between Fine Particulate Matter, Weather, and Traffic Conditions on Taft Avenue during the Covid-19 Pandemic - Baldivia, Patricia Erin Bailey H. (Animo Repository, 2022)
In light of the COVID-19 pandemic, an Enhanced Community Quarantine (ECQ) was imposed from August 6 to August 20, 2021 in the National Capital Region of the Philippines. With an imposed lockdown, the air pollution levels in a metropolitan area may have decreased. Hence, the study focused on finding a correlation between the air pollution concentrations, weather, and traffic conditions on Taft Avenue from August 1 to 14 and September 5 to October 2, 2021. To do so, the researchers have utilized real-time data on fine particulate matter (PM2.5), weather, and traffic conditions using Google Maps, Weather Underground, IQAir, and from the Air Quality Monitoring System (AQMS) of the Environment and Remote Sensing Research Laboratory (EARTH) located at De La Salle University. Most correlations between PM2.5 concentrations, weather parameters, and traffic conditions were found to have low to moderate correlation with each other. There were also differences between the correlation of PM2.5 concentrations from IQAir and EARTH with traffic and weather parameters which might be due to the fact that the location of their stations vary.